How does the first step transform into the second step. I have no idea :(
If A = B*C
then B-1A = B-1B*C
But B-1B = I
so that C = B-1A
I still don't understand where the E/1-v^2 comes from.
also its asked to prove shear strain, ill use this symbol for it. ω
it asks to prove τxy (tau xy) = (E/1-v^2) [((1-v)/2) (ωxy)]
given ωxy = 1/G (τxy)
Any help? :(
Starting with the first equation, first multiply the 1/E into the 2x2 matrix. Then find the inverse of that matrix, then factor out the constant term.
Sorry, I'm not familiar with the mechanics of shear strain theory. However, if it's just a mathematical proof that's required and all the terms and operators are completely defined, then I'm sure that someone here can help you with the mathematics.
Separate names with a comma.